Between Equality and Hierarchy: A Socio-Legal Analysis of Employment Protection for PPPK Under Indonesia’s State Civil Apparatus Reform - Herry Febriadi; Krisnadi Nasution; Syofyan Hadi (Baileo: Jurnal Sosial Humaniora, 2026)
This study aims to examine the socio-legal paradox of equality and hierarchy within Indonesia’s civil service reform under Law No. 20 of 2023, which formally establishes parity between Civil Servants (PNS) and Government Employees with Employment Agreements (PPPK). Employing a socio-legal approach that combines normative juridical analysis with empirical sociological inquiry, data were drawn from statutory documents (Law No. 20/2023, Government Regulation No. 49/2018, and related regulations), policy reports, media interviews, and PPPK testimonies. These were analyzed qualitatively through triangulation of legal norms, bureaucratic practices, and social contexts. The findings reveal that while the 2023 ASN Law normatively affirms equal rights, obligations, and career development opportunities, bureaucratic structures continue to preserve hierarchical distinctions, positioning PPPK as second-tier employees. Cultural and institutional discrimination persists, driven by an administrative–technical legal rationality that fails to achieve emancipatory transformation within the bureaucracy. The study’s novelty lies in applying a socio-legal perspective to Indonesia’s public employment reform, illuminating the dialectical relationship between law and social hierarchy. Theoretically, it enriches discourse on public employment justice and the sociology of legal reform in developing states, while practically, it provides a conceptual basis for inclusive and merit-based regulatory design in Indonesia’s civil service governance.